Foreign language lessons in an institution of higher education as an important factor in the formation of studentsʼ leadership competence - A. Zhukova (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки, 2023)
The article examines the specifics of leadership competence formation during the teaching of a foreign language in a higher educational institution. The urgency of the problem stated in the article is due to the need to train a new generation of leading specialists with high foreign language proficiency and preparedness for effective activity in a dynamic external environment. The purpose of the research is to study the specifics of leadership competence formation in the process of teaching a foreign language in higher educational institutions. The object of this study is the process of teaching a foreign language in a higher educational institution, while the subject is the need to develop leadership competence among students. The study paid special attention to the analysis of the concept of “leadership competence.”